Energy demand model for Volta River Authority - Boachie, Vincent Yiadom (2011)
A Thesis submitted to the Department of Information Systems and Decision Sciences,Kwame Nkrumah University of Science and Technology in partial fulfilment of the of requirements for the degree, 2008